PERANCANGAN APLIKASI TELEMEDICINE PELAYANAN TERINTEGRASI ANTARA PUSKESMAS DENGAN RUMAH SAKIT UMUM BERBASIS WEB - Madison Pardede (CV. Multi Kreasi Media, 2024)
Design of Telemedicine Application Integrated Services between Puskesmas and Web Berbasis General Hospitals are applications that help patient services in Puskesmas hospitals with hospitals with the help of applications, where this telemedicine application can be used for emergency requests, send referrals, patient information, receive referrals, chat, chat (message), doctor's consultation, emergency, doctor login. Where previously the service of the Puskesmas Hospital and RSUD was carried out manually. For the current Corona Pandemi, the Telemedicine application was highly recommended to be used to make services to patients to narrow the spread of the corona virus, in accordance with the government's recommendation not to be in direct contact or crowded. This application is also very helpful Puskesmas Hospital, where the tools and supplies of hospital staff that are not available at the Puskesmas can be asked for assistance to hospitals that have quite complete hospital officers and tools through the assistance of telemedicine applications. The method I use is the Waterfall.System Method Application Telmedetion I built in a website -based.